Communication factors affecting stakeholder perception of environmental problems in Silang-Santa Rosa sub-watershed - Lomboy, Olga C. (The Philippine Journal of Development Communication, 2014)
Communication can be used to make stakeholders aware of and appreciate the importance of Laguna Lake and watershed and to be responsible stewards. Knowledge about information exposure and stakeholder perception of environmental problems guides a communicating planning. This study determined the relationship between these two variables. Selected through stratified random sampling, researchers and enumerators interviewed 360 household heads face-to-face in the Silang-Sta. Rosa sub watershed. Analysis of data included frequency counts, percentages, mean scores, and Spearman Rho and Kruskall Wallis tests. Results indicated that majority did not search about environmental concern. The few information seekers used television often to know the problems of the lake and the immediate environment. Perceived problems focused on water quality of lake, pollution, soil erosion, floods, and damages to land. Perception was mostly neutral with some problems strongly or weakly perceived. Source and frequency of seeking information influenced perception of environmental problems. Recommendations for communication programs that facilitate ways to rehabilitate and manage a watershed are provided.